The Struggle to Organize Stelco and Dofasco - Storey, Robert (Relations industrielles / Industrial Relations, 1987)
This paper examines the evolution of industrial unionism in Canada during the 1930s and 1940s through a comparative analysis of events at the Steel Company of Canada (Stelco) and Dominion Foundries and Steel (Dofasco).